The Origin of Vasomotion and Stochastic Resonance in Vasomotion - Liu, Shuhong; Zhao, Liangjing; Liu, Yang (Frontiers in Bioengineering and Biotechnology, 2022)
Vasomotion is the spontaneous time-dependent contraction and relaxation of micro arteries and the oscillating frequency is about 0.01 - 0.1 Hz. The physiological mechanism of vasomotion has not been thoroughly understood. From the dynamics point of view, the heartbeat is the only external loading exerted on the vascular system. We speculate that the nonlinear vascular system and the variable period of the heartbeat might induce the low-frequency vasomotion. In this study, the laser Doppler flowmeter is used to measure the time series of radial artery blood flow and reconstructed modified time series that has the same period as the measured time series but different heartbeat curves. We measured the time series of radial artery blood flow in different conditions by adding different noise disturbances on the forearm, and decomposed the experiment pulse signal by Hilbert–Huang transform. The wavelet spectral analyses showed that the low-frequency components were induced by the variable period but independent of the shape of the heartbeat curve. Furthermore, we simulated the linear flow in a single pipe and the nonlinear flow in a piping network and found that the nonlinear flow would generate low-frequency components. From the results, we could deduce that the variable period of heartbeat and the nonlinearity of the vascular system induce vasomotion. The noise has effects on the blood signals related to the respiratory activities (~0.3 Hz), but little influence on that related to the cardiac activities (~1 Hz). Adding white noise then stopping would induce an SNR increase in the frequency band related to vasomotion (~0.1 Hz).